DIFFICULTIES IN RELATIONSHIPS AMONG PEOPLE FROM DIFFERENT CULTURES IN THE SAME COMPANY - Barros Neto, João Pinheiro de; Tanabe, Giselle Angelo (Encontro Internacional de Gestão, Desenvolvimento e Inovação (EIGEDIN), 2024)
The article discusses the challenges of intercultural communication in the workplace, emphasizing its relevance in a globalized context. By investigating the difficulties in interaction between Brazilians and foreigners, the study identifies the lack of integration and insertion programs as major obstacles. Presenting hypotheses about the difficulties in creating bonds and communication, the work highlights the importance of specific approaches and integration activities to overcome such barriers. Additionally, it explores cultural diversity and inclusion as ongoing processes that require effort and dedication. The research reveals the predominance of cultural, linguistic, and personal experience elements in forming bonds and communication. The results suggest that informal activities, language courses, and social events can promote a more inclusive environment. Based on quantitative and qualitative analyses, it is concluded that intercultural relationships in the workplace face significant challenges, but effective strategies can facilitate integration and promote a more harmonious coexistence. However, the study acknowledges the limitations of the sample size, emphasizing the need for further research to generalize the results and improve organizational practices related to cultural diversity and inclusion.